Utilisation of Agricultural Wastes as Alternative Raw Materials in Fermented Food Production - Rissa Megavitry; Silamat, Eddy (Westscience Press, 2024)
The increasing demand for sustainable food production has led to a growing interest in the utilization of agricultural wastes as alternative raw materials in the fermentation industry. This systematic literature review examines the potential of agricultural by-products, such as fruit peels, vegetable scraps, and cereal residues, as substrates for fermented food production. By analyzing a wide range of studies, this review identifies the types of agricultural wastes successfully used, the fermentation processes involved, and the benefits derived from these practices, including waste reduction, cost savings, and nutritional enhancement. The review also highlights the challenges associated with the variability in waste composition, logistical constraints, and consumer acceptance. The findings suggest that the utilization of agricultural wastes in fermented food production not only contributes to environmental sustainability but also offers economic and nutritional benefits. However, further research is needed to optimize fermentation processes, assess economic feasibility, and enhance consumer acceptance. This review provides valuable insights for researchers, industry stakeholders, and policymakers interested in promoting sustainable food production practices.